2019
DOI: 10.18632/aging.102124
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the associations of placental epigenetic aging with fetal growth

Abstract: Identifying factors that influence fetal growth in a sex-specific manner can help unravel mechanisms that explain sex differences in adverse neonatal outcomes and in-utero origins of cardiovascular disease disparities. Premature aging of the placenta, a tissue that supports fetal growth and exhibits sex-specific epigenetic changes, is associated with pregnancy complications. Using DNA methylation-based age estimator, we investigated the sex-specific relationship of placental epigenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…Indeed, maternal chronological age is prognostic of birth outcomes [17][18][19][20][21], while less clear is the role of aging biology. Accelerated placenta epigenetic aging, as indexed by the Horvath clock, has been associated with lower birthweight [28]. In parallel, the placenta also can experience telomere length shortening that induces cellular senescence and the release of secretory factors (senescenceassociated secretory phenotype) that promote parturition through increased inflammatory signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, maternal chronological age is prognostic of birth outcomes [17][18][19][20][21], while less clear is the role of aging biology. Accelerated placenta epigenetic aging, as indexed by the Horvath clock, has been associated with lower birthweight [28]. In parallel, the placenta also can experience telomere length shortening that induces cellular senescence and the release of secretory factors (senescenceassociated secretory phenotype) that promote parturition through increased inflammatory signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, several underpinning mechanisms may modulate sex differences in placental responses. Differences in DNA methylation or other epigenetic changes can cause such differences (Gabory et al, 2012; Gabory, Roseboom, Moore, Moore, & Junien, 2013; Gallou‐Kabani et al, 2010; Rosenfeld, 2012; Tarrade, Panchenko, Junien, & Gabory, 2015; Tekola‐Ayele et al, 2019). Changes in the expression of miR represent another type of epigenetic change, as detailed above.…”
Section: Introductionmentioning
confidence: 99%
“…Placental epigenetic age acceleration was determined using a published aging "clock" estimation method [35]. We have previously shown that the methylation age of the placenta is significantly correlated with gestational age of the placenta [36]. Given the sex-biased effects of placental epigenetic age acceleration on fetal growth [36], we tested the correlation between ITPR1 gene expression and placental epigenetic age acceleration separately in male and female fetuses.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…We have previously shown that the methylation age of the placenta is significantly correlated with gestational age of the placenta [36]. Given the sex-biased effects of placental epigenetic age acceleration on fetal growth [36], we tested the correlation between ITPR1 gene expression and placental epigenetic age acceleration separately in male and female fetuses. We found a significant inverse correlation between ITPR1 gene expression and placental epigenetic age acceleration among male fetuses (r = -0.4, P = 0.01) but not among female fetuses (r = 0.05, P = 0.79) (Fig 4).…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation